2022
DOI: 10.1371/journal.pone.0275424
|View full text |Cite
|
Sign up to set email alerts
|

Depression among people with dyspepsia and H. pylori infection: A community based cross-sectional study in Ethiopia

Abstract: Background Depression is the most common mental health problem, and frequently associated with physical illnesses. A link between depression, dyspepsia and Helicobacter pylori (H. pylori) infection has previously been reported. However, there is limited data regarding the association between these conditions from sub-Saharan Africa where they are highly prevalent. Objective This study aimed at elucidating the potential associations between depression, dyspepsia and H. pylori infection in Ethiopia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Furthermore, infection with H. pylori is strongly linked to mental illnesses, notably anxiety and depression. The prevalence of depression among H. pylori patients in Ethiopia was 11.9%, in Turkey 24.1%, and in Bahrain 32.1% [7][8][9]. A Japanese study found that there is a high risk of psychological distress or depressive mood among H. pylori-associated atrophic gastritis (AG)-infected females aged <50 years [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, infection with H. pylori is strongly linked to mental illnesses, notably anxiety and depression. The prevalence of depression among H. pylori patients in Ethiopia was 11.9%, in Turkey 24.1%, and in Bahrain 32.1% [7][8][9]. A Japanese study found that there is a high risk of psychological distress or depressive mood among H. pylori-associated atrophic gastritis (AG)-infected females aged <50 years [10].…”
Section: Introductionmentioning
confidence: 99%